2020
DOI: 10.1093/ejo/cjaa010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-treatment changes with and without retention in adolescents treated for maxillary impacted canines—a randomized controlled trial

Abstract: Summary Objective To evaluate whether retention is needed after orthodontic treatment of impacted maxillary canines. Trial design Two-arm parallel group single-centre randomized controlled trial. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These results differ from the literature that reports that the use of retainers can cause more discomfort, 7 although studies have highlighted that fixed maxillary retainers may not make a long-term difference in terms of maxillary incisor alignment. 15 , 30 Thus, it seems clear that prolonged use of upper retainers needs to be discussed. It is important to emphasize that the assessment of the quality of life can be influenced by several variables, including characteristics related to malocclusion that can influence the retention protocol, dental conditions involving episodes of pain, caries, periodontal problems, in addition to economic, social factors, cultural and implications of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results differ from the literature that reports that the use of retainers can cause more discomfort, 7 although studies have highlighted that fixed maxillary retainers may not make a long-term difference in terms of maxillary incisor alignment. 15 , 30 Thus, it seems clear that prolonged use of upper retainers needs to be discussed. It is important to emphasize that the assessment of the quality of life can be influenced by several variables, including characteristics related to malocclusion that can influence the retention protocol, dental conditions involving episodes of pain, caries, periodontal problems, in addition to economic, social factors, cultural and implications of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 Fixed retainers bonded canine to canine seem to be effective in maintaining the alignment of the lower incisors, while in the maxilla there are doubts about the need to use retainers in the long term. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent randomised controlled trial, 63 patients that were randomised to either retainers or no retainers were compared, but this time in the maxillary arch. 16 At the end of treatment, the patients allocated to 'no retainers' had the wire removed, but the brackets left in situ. They were then monitored firstly after two weeks and then after ten weeks, and if no changes or very minor changes (contact point displacement less than 2 mm) occurred, they were presumed to be relatively stable and the remaining brackets were removed.…”
Section: B) Stimulation Of Rank On the Osteoclast Surface By Rankl Is Essential For Osteoclast Formation And Bone Resorption Rank Is Alsomentioning
confidence: 99%
“…Retention is considered crucial in avoiding orthodontic relapse and maintaining successful treatment outcomes, as a previous study reported significant differences between a non-retention group and a retention group during a 1-year follow-up. 1 Fixed lingual retainers (FLR), first introduced by Rupert W. Knierim in 1973, are the most commonly used method by orthodontists to achieve retention. 2 Metal wire and fiber-reinforced composite (FRC) materials are widely used by orthodontists in current dental practice to make retainers.…”
Section: Introductionmentioning
confidence: 99%